ANALISIS IMPLEMENTASI MODEL KOOPERATIF TEAM ASSISTED INDIVIDUALIZATION (TAI) DALAM MENINGKATKAN KETERAMPILAN MEMAHAMI AYAT-AYAT AL-QUR’AN PADA SISWA KELAS X2 DI SMA IT BAITUL MUSLIM LABUHAN RATU - Titin Dewiaminah; Jamiluddin Yacub (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
ABSTRACT Low student engagement in learning activities and difficulties in understanding Qur’anic verses remain significant challenges in Islamic Religious Education. This study aims to describe the implementation of the Team Assisted Individualization (TAI) cooperative learning model in improving students’ skills in understanding Qur’anic verses among Grade X2 students at SMA IT Baitul Muslim Labuhan Ratu. The study employed a qualitative approach with a descriptive method. The research subjects consisted of 35 students. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the implementation of the Team Assisted Individualization (TAI) model increased students’ engagement in the learning process, as reflected in their active participation in asking questions, expressing opinions, engaging in discussions, and collaborating within learning groups. The model also assisted students in understanding the meanings of Qur’anic verses, identifying the values contained within them, and relating these teachings to everyday life. The formation of heterogeneous learning groups fostered more effective and collaborative interactions among students, resulting in a more active learning environment. Although challenges were encountered, including differences in students’ academic abilities and limited instructional time, the TAI model proved effective in supporting the improvement of students’ skills in understanding Qur’anic verses and creating a more effective learning atmosphere. These findings suggest that the TAI model can serve as a relevant cooperative learning alternative for enhancing the quality of Islamic Religious Education at the secondary school level. ABSTRAK Rendahnya keterlibatan siswa dalam pembelajaran serta kesulitan memahami ayat-ayat Al-Qur’an menjadi tantangan dalam pembelajaran Pendidikan Agama Islam. Penelitian ini bertujuan mendeskripsikan implementasi model pembelajaran kooperatif tipe Team Assisted Individualization (TAI) dalam meningkatkan keterampilan memahami ayat-ayat Al-Qur’an pada siswa kelas X2 SMA IT Baitul Muslim Labuhan Ratu. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif. Subjek penelitian terdiri atas 35 siswa. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penerapan model Team Assisted Individualization (TAI) meningkatkan keterlibatan siswa dalam proses pembelajaran melalui aktivitas bertanya, menyampaikan pendapat, berdiskusi, dan bekerja sama dalam kelompok. Model ini juga membantu siswa memahami makna ayat, mengidentifikasi nilai-nilai yang terkandung dalam ayat Al-Qur’an, serta mengaitkannya dengan kehidupan sehari-hari. Pembentukan kelompok belajar yang heterogen mendorong terjadinya interaksi yang lebih efektif dan kolaboratif antarsiswa sehingga proses pembelajaran berlangsung lebih aktif. Meskipun terdapat kendala berupa perbedaan kemampuan akademik siswa dan keterbatasan waktu pembelajaran, model TAI terbukti mendukung peningkatan keterampilan memahami ayat-ayat Al-Qur’an dan menciptakan suasana belajar yang lebih efektif. Temuan ini menunjukkan bahwa model TAI dapat menjadi alternatif pembelajaran kooperatif yang relevan untuk meningkatkan kualitas pembelajaran Pendidikan Agama Islam di tingkat sekolah menengah.